Farming Hope-Eau Claire - Riedesel, Eva; Widmer, Kathleen; Peterson, Kelly; Pettit, Lindsey; Moore, Kaitlyn; Fernandes, Jill Hecker (My University, 2017)
Farming Hope is an organization created in El Salvador, built on the premise that all human beings have potential. Homelessness, mental health, and food deprivation are prevalent problems universally. Farming Hope aims to decrease these prevalent problems by building vocational skills and purpose in these individual’s lives.
Color poster with text, photos, and images.
Keywords: Soup kitchens; Homeless; Community gardens; Posters